2016
DOI: 10.1002/pbc.25954
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents with Cancer in Italy: Improving Access to National Cooperative Pediatric Oncology Group (AIEOP) Centers

Abstract: This analysis compared the numbers of patients treated at Italian pediatric oncology group (Associazione Italiana Ematologia Oncologia Pediatrica [AIEOP]) centers with the numbers of cases predicted according to the population-based registry. It considered 32,431 patients registered in the AIEOP database (1989-2012). The ratio of observed (O) to expected (E) cases was 0.79 for children (0-14 years old) and 0.15 for adolescents (15-19 years old). The proportion of adolescents increased significantly over the ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 18 publications
2
14
0
1
Order By: Relevance
“…These reasons explain the importance to make a Network Campania of Pediatric Oncology (NETCOP) in order to do more efficacy the collaboration between the regional centers of pediatric oncology (Hub centers) and pediatric hospitals present in the five province of Campania region (Spoke centers). In the next future other problem is the recruitment of immigrant children that underwent a progressive, steady increase over the years, growing from 30 cases (2 % of the total number) in 1999 to 130 cases (8 % of the total number) in 2008 [810]. Actually, AIEOP centers in Campania treated 2.4 % of immigrant children [5].…”
Section: Discussionmentioning
confidence: 99%
“…These reasons explain the importance to make a Network Campania of Pediatric Oncology (NETCOP) in order to do more efficacy the collaboration between the regional centers of pediatric oncology (Hub centers) and pediatric hospitals present in the five province of Campania region (Spoke centers). In the next future other problem is the recruitment of immigrant children that underwent a progressive, steady increase over the years, growing from 30 cases (2 % of the total number) in 1999 to 130 cases (8 % of the total number) in 2008 [810]. Actually, AIEOP centers in Campania treated 2.4 % of immigrant children [5].…”
Section: Discussionmentioning
confidence: 99%
“…During 2015, there were 215 new patients with solid tumors treated at the INT's Pediatric Oncology Unit, and 84 (39%) were AYA, that is, ≥15 years old. Seventy of them were 15–19 years old: compared to the number of cases expected to occur in Italy (860 patients aged 15–19 per year), this number corresponded to 8% of all the Italian cases. This proportion was higher considering specific tumor types, for example, the Unit treated 31 patients with sarcoma in this age range (17 soft tissue sarcomas and 14 bone sarcomas), who represented 32% of the expected Italian patients (96 cases), and 17 brain tumors, accounting for 17% of 101 expected Italian cases.…”
Section: Resultsmentioning
confidence: 95%
“…Another finding was that the majority of the AYA patients diagnosed with a malignancy at our Unit in 2015 were included in clinical trials. This outcome is hugely important because it has been variously reported that AYA are generally less likely than children to be enrolled in clinical protocols . Programs tailored to AYA should aim both to ensure their best clinical management and to provide for their psychosocial support needs (e.g., age‐specific psychosocial support facilities, dedicated spaces, recreational events), but the latter would be insufficient if patients are unable to enter clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first draft of a national-scale project was developed by the Italian Scientific Society of Pediatric Oncology (Associazione Italiana Ematologia Oncologia Pediatrica [AIEOP]). From 2007 to 2010, a work group concentrated primarily on dealing with the problem of adolescents' limited access to clinical protocols and the barriers posed by age limits for admissions to pediatric oncology departments (19)(20)(21)(22) (23). This organization has obtained the official support of the Italian Ministry of Public Health, and established an important partnership with a major charity, the Fondazione Umberto Veronesi (FUV).…”
Section: Introductionmentioning
confidence: 99%